Frequent use of online medical records: analysis of influence factors based on structural equation modeling - Wei Wang; Lei Qin; Lei Qin; Yang Chen; Yinzhi Wang; Linglong Ye; Ruojia Wang; Yingqiu Zhu (Frontiers in Public Health)
The advent of electronic storage of medical records and the internet has led to an increase in the use of online medical records, thereby enhancing doctor–patient communication and facilitating medical treatment. Based on demographic and personal behavioral characteristics from the National Cancer Institute’s 2019–2020 National Trends in Health Information Survey data, this study explored the characteristics and factors influencing the frequent use of online medical records and compared them with those that do not. By combining traditional statistical tests and two machine learning algorithms, eight variables were identified as key variables in the frequent use of online medical records. These variables were then divided into three influencing factors (latent variables). The structural equation model was used to conduct impact path analysis of the three influencing factors and target variables. The three impact factors were (1) Whether to provide online medical records, (2) Degree of concern for health, and (3) Whether to use internet. This paper proposes recommendations based on the three impact factors, thereby promoting the usefulness of medical records in a larger group of people.